Biological Response to Wollastonite Doped alpha-Tricalcium Phosphate Implants in Hard and Soft Tissues in Rats - Minarelli Gaspar, A. M. [UNESP]; Saska, S. [UNESP]; Carrodeguas, R. G.; De Aza, A. H.; Pena, P.; De Aza, P. N.; De Aza, S. (Trans Tech Publications Ltd, 2009)
The biological response following subcutaneous and bone implantation of beta-wollastonite(beta-W)-doped alpha-tricalcium phosphate bioceramics in rats was evaluated. Tested materials were: tricalciurn phosphate (TCP), consisting of a mixture of alpha- and beta-polymorphs; TCP doped with 5 wt. % of beta-W (TCP5W), composed of alpha-TCP as only crystalline phase; and TCP doped with 15 wt. % of beta-W (TCP15), containing crystalline alpha-TCP and beta-W. Cylinders of 2x1 mm were implanted in tibiae and backs of adult male Rattus norvegicus, Holtzman rats. After 7, 30 and 120 days, animals were sacrificed and the tissue blocks containing the implants were excised, fixed and processed for histological examination. TCP, TCP5W and TCP15W implants were biocompatible but neither bioactive nor biodegradable in rat subcutaneous tissue. They were not osteoinductive in connective tissue either. However, in rat bone tissue beta-W-doped alpha-TCP implants (TCP5W and TCP15W) were bioactive, biodegradable and osteoconductive. The rates of biodegradation and new bone formation observed for TCP5W and TCP15W implants in rat bone tissue were greater than for non-doped TCP.
Keywords: Calcium phosphate; wollastonite; in vivo test; biocompatibility